Gene Duplications in the Genomes of Staphylococci and Enterococci - Sanchez-Herrero, José Francisco; Bernabeu, Manuel; Prieto, Alejandro; Hüttener, Mário; Juárez, Antonio (Frontiers in Molecular Biosciences, 2020)
Gene duplications are a feature of bacterial genomes. In the present work we analyze the extent of gene duplications in the genomes of three microorganisms that belong to the Firmicutes phyluym and that are etiologic agents of several nosocomial infections: Staphylococcus aureus, Enterococcus faecium and Enterococcus faecalis. In all three groups, there is an irregular distribution of duplications in the genomes of the strains analyzed. Whereas in some of the strains duplications are scarce, hundreds of duplications are present in others. In all three species, mobile DNA accounts for a large percentage of the duplicated genes: phage DNA in S. aureus, and plasmid DNA in the enterococci. Duplicates also include core genes. In all three species, a reduced group of genes is duplicated in all strains analyzed. Duplication of the deoC and rpmG genes is a hallmark of S. aureus genomes. Duplication of the gene encoding the PTS IIB subunit is detected in all enterococci genomes. In E. faecalis it is remarkable that the genomes of some strains encode duplicates of the prgB and prgU genes. They belong to the prgABCU cluster, which responds to the presence of the peptide pheromone cCF10 by expressing the surface adhesins PrgA, PrgB and PrgC.